Pengaruh Return On Asset Dan Debt To Equity Ratio Terhadap Price Earning Ratio - Mira Firdiyanti; Hani Fitria Rahmani (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
The objective of this research is to examine the impact of ROA (Return on Assets) and DER (Debt to Equity Ratio) on the Price Earning Ratio (PER) in manufacturing companies operating in the Food and Beverage subsector and listed on the Indonesia Stock Exchange between 2017 to 2021. The study adopts a quantitative approach with the utilization of multiple linear regression analysis. The findings of the investigation demonstrate that both ROA and DER exert a significant influence on PER, both collectively and individually.